ChemInform Abstract: Polyether Complexes of Groups 13 and 14. Issue 36 (August 2016) - Swidan, Ala'aeddeen; Macdonald, Charles L. B.
Abstract: Review: notable aspects of the chemistry of polyether complexes of group 13 and 14 elements; 191 refs.